Penyuluhan Penyakit Dismenorea Primer Pada Remaja Putri di SMK Barunawati Surabaya - Sa'adah, Alfina Aisatus (Jurnal Abdimas Jatibara, 2022)
Primary Dysmenorrhea is a menstrual pain that is not associated with gynecological disorders. Dysmenorrhea or menstrual pain can cause women to be unable to carry out daily activities such as not being able to do housework, not coming to work, and for students it can reduce concentration and motivation to learn, it can even cause students not to go to school. Therefore, the problem of dysmenorrhea must be addressed immediately so as not to harm women who often experience dysmenorrhea. The purpose of this community service is that the participants can understand about primary dysmenorrhea in adolescent girls. The type of community service used is by conducting counseling methods. The target data for this community service activity are young women in class XI at SMK Barunawati Surabaya. Based on the results of community service at SMK Barunawati Surabaya, it was found that before the counseling was carried out, students did not understand primary dysmenorrhea for class XI OTKP 1 by 73.3% while class XI OTKP 2 was 100%. After counseling, there was a decrease in student data that did not understand primary dysmenorrhea for class XI OTKP 1 by 63.3% while class XI OTKP 2 was 48%. The data were obtained from pre-test and post-test questions that were done by students.